Technology: Saving and Enriching Life During COVID-19 - Sinha, Shubhra; Verma, Ankita; Tiwari, Priyanka (Frontiers in Psychology, 2021)
The pandemic of COVID-19 has arrested the life of 7.8 million people living on this earth. However, some people are more vulnerable to the risk of this deadly virus. The frailty of senior citizens put them at the top of this list. The past six months have not only presented a threat to their physical health but to mental health also. Although lockdown was necessary to check the spread of the coronavirus it culminated in an exponential rise in the problems of loneliness, anxiety, fear, helplessness, and depression. The present paper reviews the role of social networking sites, apps, and other digital platforms in saving and enriching the lives of the elderly, especially those who spent the lockdown alone and were devoid of a regular support system due to unavailability of transport and administrative restrictions on the movement of people. It also analyzes the efficiency of the virtual world in reducing their anxiety of being alone by connecting them with others and also make them feel empowered. The review is based on the online data available about the insurgence in the percentage of elderly people using such platforms, recent studies analyzing the effects of the COVID 19 pandemic on senior citizens. Besides this personal telephonic discussions were conducted with some elderly people who spent their lockdown alone in their homes. The study was primarily focused on three objectives. Firstly it attempts to understand the ways in which senior citizens made use of social networking sites and various digital platforms for managing life better. Secondly, it analyses the process of adopting technology, and finally, it examined the width and depth of the impact technology created in their life and also the permanence of this change. The analysis clearly suggests an increase in the digital life of elderly people. The process moved in distinct stages from utter confusion to relative ease in using technology, thereby significantly reducing the loneliness, and bringing relatively stable change in the way they lead their life.